The Quantitative Analysis for Road networks in Karbala Governorate - مهيب كامل فليح دينا مكي ابراهيم (College of Education for Women, 2019)
The road networks is considered to be one of the determinants that controls to specify the areas of human activities, which it depend on to specify the arrival cost , in addition it is useful to achieve the connectivity for interaction and human activities , and shorten the distance and time between the population and places of service. The density of the road network in any space directly affected by the density of population and the type of economic activities and administrative functions performed by the space. On this basis, the subject of this study is reflected in the quantitative analysis of the roads network in the Governorate of Karbala. The study consists the quantitative analysis for the roads network and the Urban Nodes in the Governorate. This study aims to know the density of the road networks and to specify the degree of centralization for the Urban Nodes in Karbala Governorate, as well as the possibility to measure the accessibility between nodes of network and arranged hierarchy as well as the degree of interdependent.